Effect of Different Bag Opening Methods of Oyster Mushroom (Pleurotus ostreatus) on Growth Parameter, Yield and Benefit Cost Ratio - G. K. Upamanya; R. Brahma; R. Sarma; P. Sharma; K. Das (International Journal of Economic Plants)
Oyster mushroom growers are generally confused about the scientific basis of the cultivation technology with regard to the best bag opening method after a spawn run.  The present study was undertaken to find out the effect of four different methods of bag opening on yield, benefit cost ratio (BCR) and biological efficiency of oyster mushrooms during November, 2020 to March, 2021. The results indicated that treatment-2 (retaining the polythene bag for the entire cultivation period) exhibited significantly the highest yield (1644.61 g bed-1) followed by treatment-3 (opening top part of the polythene bag after spawn run) (1536.62 g bed-1), and treatment-1 (opening top and bottom part of the polythene bag (1468.82 g bed-1) and treatment-4 (complete removal of the polythene bag) (1111.19 g). The BCR was also found to be the highest (4.39) in treatment-2 followed by treatment-3 (4.09), treatment-1 (3.96) and treatment-4 (2.98). Retaining the polythene bag during the entire cultivation period was found to be the best method of cultivation with regard to biological efficiency (82.23%). Opening the top part of the polythene bag after the spawn run showed the biological efficiency of 76.83% which was followed by the treatment with opening the polythene bag from the top and bottom part of the bed (73.44%).The lowest biological efficiency (55.56%) was observed in the treatment in which the entire polythene bag was removed after a spawn run in darkroom. Mushroom growers may retain the polythene bag surrounding the mushroom bed during the entire cultivation period for better economic return.